2017
DOI: 10.1080/1331677x.2017.1392886
|View full text |Cite
|
Sign up to set email alerts
|

Sector-specific gender pay gap: evidence from the European Union Countries

Abstract: The study aims to determine whether the unexplained gender wage gap varies in the different sectors of the economy and to identify the possible causes of these differences. Firstly, we estimate average treatment effect on the individual sectors to identify the unexplained part of gender pay gap. To identify the possible causes of observed variability in unexplained gender wage differences, we use a linear regression model. Using European Union Statistics on Income and Living Conditions (EU-SILC) data for 24 Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Another factor influencing the gender pay gap is the composition of the management. It turns out, that more diversity in corporate management is beneficial for decreasing the gender pay gap (Ahamed et al, 2019;Mostak, 2019;Rabovsky and Lee, 2018;Carter et al, 2017;Hedija, 2017). Similar opinion is presented by Stojmenovska (2018), who, according to the research carried out, confirms that an increase in the percentage of female managers in the workplace is associated with decreasing the gender pay gap.…”
Section: Level Of Women and Men Remunerations In Researchmentioning
confidence: 60%
See 2 more Smart Citations
“…Another factor influencing the gender pay gap is the composition of the management. It turns out, that more diversity in corporate management is beneficial for decreasing the gender pay gap (Ahamed et al, 2019;Mostak, 2019;Rabovsky and Lee, 2018;Carter et al, 2017;Hedija, 2017). Similar opinion is presented by Stojmenovska (2018), who, according to the research carried out, confirms that an increase in the percentage of female managers in the workplace is associated with decreasing the gender pay gap.…”
Section: Level Of Women and Men Remunerations In Researchmentioning
confidence: 60%
“…In the literature on the subject, it is also pointed out that gender pay gap varies from one economic sector to another and from one country to another (Hedija, 2017). The average unjustified gender pay gap is the lowest in public administration and defense and the highest in construction and agriculture, forestry and fishery.…”
Section: Level Of Women and Men Remunerations In Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of papers adopt a cross-country perspective. Using European Union Statistics on Income and Living Conditions (EU-SILC) data for 24 European Union members, Hedija (2017Hedija ( , pp. 1804Hedija ( -1819 showed that the gender pay gap varies among the countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One aspect of the gender pay gap that has received very little attention so far concerns its regional dimension. Empirical studies mostly focus on the national level (for example, Jurajda, 2003 for the Czech Republic and Slovakia; Pena-Boquete, De Stefanis, Fernandez-Grela, 2010 for Italy and Spain; Chatterji, Mumford, Smith, 2011 for the United Kingdom; Śliwicki, Ryczkowski, 2014 for Poland) or adopt a cross-country perspective (Olivetti, Petrongolo, 2008;Hedija, 2017;Boll, Lagemann, 2019). However, the gender pay gap varies considerably within a country.…”
Section: Introductionmentioning
confidence: 99%